TECHNOLOGY OF ELASTIC ANISOTROPY STUDY OF ROCKS FOR SOLVING GEOLOGICAL PROBLEMS - Bezrodnyi, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The texture analysis of acoustic technology, which is based on the petroacoustic research and consists of two parts: the experimental measurements of velocities of quasi-longitudinal and quasi-processing waves and interpretation of results are given. The method makes it possible to obtain detailed information about the anisotropy of elastic waves in rocks, the elastic symmetry and texture of rocks, a sequence of deformation and tectonic nature of the conditions of their formation and transformation, etc.